2006
DOI: 10.1196/annals.1368.019
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SNPs in the Plasma of Pregnant Women and in the Urine of Kidney Transplant Recipients by Mass Spectrometry

Abstract: Recently, it has been discovered that cell-free fetal DNA is smaller than corresponding maternal DNA. Therefore, circulating fetal DNA can be enriched by size-fractionation. Such a selection improves the non-invasive prenatal diagnosis of paternally inherited single gene mutations. Recent studies showed that MALDI-TOF mass spectrometry (MS) can be used to reliably detect fetal-specific single-nucleotide polymorphisms (SNPs) in maternal plasma. In this study, we looked at whether the size-fractionation approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…One such example is the detection of paternally inherited SNPs located in the β-globin locus for NIPD of β-thalassemia [57,58]. Furthermore, the application of PCR technology in combination with mass spectrometry (MS) has allowed the detection of fetal monogenic mutations present in the maternal circulation [57-63]. One such application was the use of the MassARRAY system, a matrix-assisted laser desorption ionization time-of-flight MS system designed for the detection of primer-extended PCR products [62,64].…”
Section: Developments In Aneuploidy Detectionmentioning
confidence: 99%
“…One such example is the detection of paternally inherited SNPs located in the β-globin locus for NIPD of β-thalassemia [57,58]. Furthermore, the application of PCR technology in combination with mass spectrometry (MS) has allowed the detection of fetal monogenic mutations present in the maternal circulation [57-63]. One such application was the use of the MassARRAY system, a matrix-assisted laser desorption ionization time-of-flight MS system designed for the detection of primer-extended PCR products [62,64].…”
Section: Developments In Aneuploidy Detectionmentioning
confidence: 99%
“…The concentration of fetal DNA in maternal circulation is considerably low, comprising 3.7% of total DNA as quantified by realtime quantitative analysis (17). A previous study from our laboratory also showed that donor-derived genetic materials could be sensitively detected in the urine of kidney transplant recipients using MALDI-TOF MS (13).…”
Section: Discussionmentioning
confidence: 98%
“…It could permit the reliable detection of SNPs (11) from a very rare target, including fetal point mutations from cell-free fetal DNA in maternal plasma and donor derived cell-free DNA in organ transplant recipients urine, which cannot be reliably detected by more conventional PCRbased approaches (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the non-invasive detection of SNPs [26][27][28] and fetal CF mutations [7,[29][30] in maternal plasma. However, the techniques used in those publications require complicated handling to be applied in clinical practice or are not valid to study any mutation.…”
Section: Discussionmentioning
confidence: 99%